PENGARUH LATAR BELAKANG SOSIAL EKONOMI DAN SUASANA KERJA TERHADAP KOMITMEN KARYAWAN SERTA DAMPAKNYA PADA KUALITAS LAYANAN - Kurniawati, Dyah (Widya Warta, 2014)
The purpose of this study was to determine whether or not the socio-economic background and work atmosphere influence the quality of service with employees’ commitment as mediating variable. The population was non-educational employees who serve students. The sample was obtained using saturated sampling technique with path analysis method. The results showed that the socio-economic background and work atmosphere had direct influence toward employees’ commitment and indirect influence toward the quality of service throughemployees’ commitment. Thus, the agent should consider the socio-economic background which include education, income, and welfare as well the work environment which include interpersonal communication, employer, job description, and clear job authority, as it affects employees’ commitment and, in turn, affects the quality of service to students.